Nurse Practitioners and Sexual and Reproductive Health Services An Analysis of Supply and Demand - Auerbach, David I. (RAND Corporation, 2012)
Trends for Sexual and Reproductive Health (SRH) services in the next decade show demand outstripping supply. Policy options addressing an inadequate supply of SRH-trained Nurse Practitioners to meet future demand for SRH services include education, clinical training, accreditation, and credentialing; federal regulation and financing; state regulation and financing; and responding to emerging models of care delivery.